Efeito de um programa de equoterapia nos aspectos psicomotores de crianças com indicativos do TDAH - Barbosa, Gardenia de Oliveira (Universidade Federal de São Carlos, 2013)
The hippotherapy is a therapeutic and educational horse that uses an interdisciplinary approach in seeking the biopsychosocial development of people with special needs. Among the various types of special needs highlights the disorder and attention deficit hyperactivity disorder (ADHD), children with this disorder characterized by a level of attention to inappropriate for their age, developmental disorder that causes motor, perceptual , cognitive and behavioral. The aim of this study is to assess the effect of a program of hippotherapy on the psychomotor development of children with ADHD indicative. Regarding the method, we developed an exploratory study of type experimental manipulation. Participants were five children aged between 7 and 10 years, coming from a city in the interior of São Paulo. In order to identify children with ADHD indicative of the scale was employed MTA SNAP-IV (ADHD rating scale for Swanson, Phelan and Nonam - version IV). Before and after the intervention period, study participants underwent an evaluation based Motor Development Scale (EDM). The intervention consisted of a program of education called equine therapy / rehabilitation, and was composed of 24 sessions, lasting 30 minutes, recorded systematically through filming and field diary. The results were analyzed quantitatively and qualitatively by the Wilcoxon paired test with p <0.05 in combination with a descriptive analysis of the evolution of the practitioners. Through the analysis of the results showed that the program influenced in all studied motor skills, and psychomotor aspects more influenced by hippotherapy program, according to the scale of motor development (EDM), were respectively spatial organization, balance, motor skills thin body schema, and the lowest was observed in the motor influence global and temporal organization. Since in the post-test, the motor age overall was statistically significant, it is concluded, in general, that the hippotherapy program was effective for the development of psychomotor aspects of children with ADHD indicative.
Keywords: Educação especial; Transtorno de déficit de atenção/hiperatividade (TDAH); Equoterapia; Desenvolvimento psicomotor; Special Education; ADHD; hippotherapy; psychomotor development; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL